Macmillan Primary Social Studies 4 - Ogunsanya, Mobolaji et al (Macmillan Nigeria Publishers Ltd, 1999)
The role of social studies in this matter is to assist parents in particular and the society at large in equipping our children especially with the attitude and value which enable them to fit into the society.
Keywords: Education Social Study